PENGARUH KOMPOS PAITAN DAN NPK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN MENTIMUN (CUCUMIS SATIVUS L.) - IRAWATY ROSALYNE (JURNAL ILMIAH SIMANTEK, 2020)
The purpose of this study is to find out the influence of Compost Paitan and NPK on the growth and production of cucumberplants (Cucumis sativus L.). Research using factorial Randomized Group Design (RAK), with 2 treatment factors where thefirst factor is the administration of paitan compost consisting of 3 levels of dosi namely K1: Compost Paitan 10 ton / ha) 1.28kg / plot, K2 : Paitan Compost Administration (20 tons / ha) 2.56 kg / plot, K3: Paitan Compost Administration (350 tons / ha)3.2 kg / plot, while for the second factor is the administration of NPK Fertilizer consisting of 3 dose levels namely N1:administration of NPK Fertilizer (250 kg / ha) 32 g / plot, N2: administration of NPK Fertilizer (3000 kg / ha) 38.4 g / plot ,N3 :the administration of NPK fertilizer ( 350 kg / ha) 44.8 g / plot Parameters observed in this study are delivered: the height ofthe plant (cm), the number of plants (fruit), the weight of fruit per plant (kg) and the production of fruit per plot. For theobservation results were observed with a fingerprint analysis on the trust hose at a rate of 5% while to use the difference intreatment used BNT test (Smallest Real Difference) with a confidence lapse at the level of 5% Of the results of the study itwas known that the treatment of Compost Paitan and NPK had a noticeable effect on the height of plants (cm) ages 2, 3, 4, 5and 6 MST. The number of fruit crops (fruit), the weight of fruit per plant (kg) and the production of fruit per plot. Paitan K3Compost Treatment (350 tons/ha) 3.2 kg/plot, showing the highest cucumber plant height aged 2, 3, 4, 5 and 6 MST. (17.22cm), (60.47 cm), (101.11 cm), (147.36 cm) and (167.69 cm), number of fruits per plant (fruit) 9.22 pieces, fruit weight perplant (kg) 2.10 kg, fruit production per plot (kg) 15.61 kg. NpK Fertilizer Treatment N3 = npk fertilizer administration ( 350 kg /ha) 44.8 g / plot shows the highest height of cucumber plants aged 2,3, 4, 5 and 6 MST respectively. (16.42 cm), (55.94 cm),(108.50 cm), (143.31 cm) and (163.36 cm), number of fruits per plant 8.82 pieces, plant fruit weight 1.88 kg, fruit productionper plot 13.81 kg.